The first Carventinae species in Miocene Dominican Amber (Hemiptera: Heteroptera: Aradidae) - Heiss, Ernst; Poinar Jr., George O. (Zootaxa, 2012)
The flat bug family Aradidae is represented to date in Dominican Amber only by two species: Calisiopsis brodzinskyorumFroeschner, 1992 and Mezira scheveni Heiss, 2000 belonging to the subfamilies Calisiinae and Mezirinae respectively.Now two fossil species sharing the characters of the extant genera Nesoproxius Usinger & Matsuda, 1959 (N.latocanusn.sp.) and Carventus Stål, 1865 (C. bechlyi n.sp.), and one tentatively assigned to Acaricoris Harris & Drake, 1944 (A.robertae n.sp.), are described and illustrated below. Another specimen cannot be placed into an extant genus, and Proneoproxius n.gen. is proposed to accommodate P.cornutus n.sp.